STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN SIKAP SOSIAL DAN SIKAP SPIRITUAL GURU DI SD AL WILDAN ISLAMIC SCHOOL 1 GADING SERPONG TANGERANG - MEYTA RAHMADANIATI (UNISAN JURNAL, 2024)
This research aims to describe the implementation of character education at the Duri Bengkalis Integrated Tsanawiyah Madrasah, Riau. Character education is becoming an increasingly important topic in the context of modern education. Character education is seen as an important aspect in developing students as individuals with character and ready to face future challenges. In its implementation, character education is still considered to be less of a priority in several educational institutions. In fact, character education can help develop students' positive interests, attitudes and behavior, which can ultimately influence student success in the future. This research aims to examine the implementation of character education management in developing students' interests, attitudes and positive behavior at school. The research was conducted using a qualitative approach with data collection techniques through interviews, observation and documentation. The research results show that effective character education management can help develop students' positive interests, attitudes and behavior at school. The implementation of character education that is integrated into the curriculum and implemented consistently can increase students' understanding of character values. In addition, the role of teachers and principals in motivating and guiding students is very important in the success of character education programs. In conclusion, this research shows that good and effective character education management can help develop students' positive interests, attitudes and behavior. Character education programs that are integrated and implemented consistently in the curriculum can help increase students' understanding of character values. The role of teachers and school principals is very important in motivating and guiding students to internalize the character values ​​taught at school. It is hoped that this research can contribute to improving the quality of character education in schools